Do Investment Strategies Matter for Trading Global Clean Energy and Global Energy ETFs? - Min-Yuh Day; Yensen Ni; Chinning Hsu; Paoyu Huang (Energies, 2022)
Based on technological innovation and climate change, clean energy has been paid increasing attention to by worldwide investors, thereby increasing their interest in investing in firms that specialize in clean energy. However, traditional energy still plays an important role nowadays, because extreme weather has often occurred in the winters of recent years. We thus explore whether investing the strategies adopted by diverse technical trading rules would matter for investing in energy-related ETFs. By employing two representative global ETFs with more than 10 years of data, iShares Global Clean Energy ETF as the proxy of clean energy performance and iShares Global Energy ETF as that of traditional energy performance, we then revealed that momentum strategies would be proper for buying the green energy ETF, but contrarian strategies would be appropriate for buying the energy ETF. Furthermore, based on investment strategies adopted by diverse technical trading rules, we showed that the performance of clean energy outperforms that of energy, indicating that green energy does matter for the economy. Moreover, while observing the price trend of these two ETFs, we found that such two ETFs may have opposite share price performances, implying that, while the green energy ETF reached a relatively high price, investors following the contrarian strategies suggested in this study may reap profits by investing the energy ETF.